Advantages of Smart Agricultural Technologies to Agricultural Enterprises Management - Kemalettin Ağızan; Zeki Bayramoğlu; Süheyla Ağızan (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study; By examining the development of technology use in agriculture, making comparisons according to countries and discussing the applicability of 4.0 technology in the agricultural sector, the advantages of these technologies to business economy and management are determined. As a matter of fact, the increase in the world population and the need for more resources accordingly keeps the issue of productivity on the agenda. Technological methods are needed to increase productivity in agricultural production. These technological methods; It is known as green agriculture, precision agriculture, digital agriculture, smart agriculture or agriculture 4.0, and with the development of these technologies, a very comprehensive data acquisition process has started and it has come to the point of making business decisions according to the analysis of the data and the results of these. At this point, the most important issue to be discussed is the applicability and affordability of smart agriculture technology. As a matter of fact, the production factors (land, capital, labor and entrepreneurship) owned by agricultural enterprises in Turkey are limited and insufficient according to European standards. Therefore, the compatibility of the technologies to be used according to the enterprises is extremely important, and strategies should be determined in order to prevent the use of idle technology. In this context, for the first time in the study, the technological development was examined by classifying the application areas of Agriculture 4.0 technology and their hardware features. As a result, predictions and suggestions about the future of Agriculture 4.0 or smart agriculture will be prepared and the smart agriculture policy will be presented to the sector and public institutions.